Anesthetic management of a patient with Mounier-Kuhn syndrome undergoing off-pump coronary artery bypass graft surgery -A case report- - Jeong Jin Min (Korean Journal of Anesthesiology, 2011)
Mounier-Kuhn-syndrome patients have markedly dilated trachea and main bronchi due to an atrophy or absence of elastic fibers and thinning of smooth muscle layers in the tracheobronchial tree. Although this syndrome is rare, airway management is challenging and general anesthesia may produce fatal results. However, only a few cases have been reported and this condition is not widely known among anesthesiologists. We present the case of a tracheobronchomegaly patient undergoing an emergency off-pump coronary artery bypass. Although the trachea was markedly dilated with numerous tracheal diverticuli, there was an undilated 2 cm portion below the vocal cords found on the preoperative CT. Under a preparation of extracorporeal membrane oxygenation, we intubated and placed the balloon of an endotracheal tube (I.D. 9 mm) at this portion, and maintained ventilation during the operation. This case showed that a precise preoperative evaluation and anesthetic plan is essential for successful anesthetic management.